Metacognitive Skills of College Students in Mathematics Problem Solving: Overview by Student's Field Dependent - Hidajat, Djatmiko; Hasbi, Muhammad; Fitri (ETDC: Indonesian Journal of Research and Educational Review, 2024)
Overall, this study aims to assess college students' field-dependent metacognitive skills in mathematics problem-solving. We administered the Group Embedded Figures and Mathematical Ability Tests to 35 future educators from a private school in Sukoharjo, Indonesia. Students' questioning of each group served to gauge their proficiency in solving problems, as shown in the results. Participants also demonstrated partially achieved metacognitive abilities, as measured by the (metacognitive) skills criterion, which encompassed tasks such as planning, monitoring, assessing, and predicting. First, the participants documented and explained the facts given in the question. Second, they checked the results against the plan. Third, they evaluated the success of the objectives by analyzing the results to make sure everything went according to plan. Finally, they predicted and stated the results of the problem-solving process. In light of these findings, researchers and teachers facing comparable obstacles would do well to delve deeper into the function of metacognitive abilities in problem-solving.